Long-term clinical remission in a patient with metastatic gastric cancer after palliative chemotherapy - Teufel, Andreas; Lehnert, Thomas; Stremmel, Wolfgang; Rudi, Jochen (Onkologie, 2000)
More than 50% of patients with gastric cancer initially present with locally advanced or metastatic disease. In general, gastric cancer in an advanced or metastatic stage is regarded as incurable. Despite treatment with palliative chemotherapy, the median survival time is still limited and does not exceed 12 months. Case Report: We report on a patient with advanced and metastatic gastric cancer who received palliative surgery and subsequent palliative chemotherapy.
Gesehen am 08.12.2021